EFEKTIVITAS PEMBELAJARAN KERUCUT BERBASIS TEORI BRUNER - Irfan, Ade; Anzora, Anzora (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
One effort that can be done to help teachers is to offer a variety of alternative learning as inspiration for teachers in teaching. As one of the learning theory, theory of Bruner could be one appropriate strategies used in improving student learning outcomes in learning the cone. To reveal the effectiveness of cone learning based on Bruner’s theory, this research uses a quantitative approach with this type of research is quasi experiment. The design of this research is the one-group pre-test-post-test design. The subject is a student of class IX Junior High School. Data collection is done with the test results of the study, observation and question form. The results showed that the activity of students to each category on each RPP is effective, the ability of teachers in managing cone learning based on Bruner’s theory is effective at RPP I achieved an average of 4.44 and on RPP II reaches an average of 4.50. Student response against cone learning based on Bruner’s theory is effective where > 80% of students gave a positive response. Student learning results indicates that 20 students (71.43%) completely studied, while the 8 students (28.57%) is not thoroughly studied. Thus it can be concluded that the mastery learning of classical learning was not met. Even so, there was a significant increase in the mastery learning in Bruner's theory with cone in classical i.e. amounting to 50%. For the students who hadn't learned i.e. 8 students (28.57%) will be given additional duties as well as remedial and homework to help students understand the material cone hadn't he learned.